Influential foreign naturalists and scientists in the development of biological sciences in Costa Rica - Quirós, Luko Hilje (Revista de Biología Tropical, 2023)
Introduction: Since the beginning of its republican life, the development of biological sciences in Costa Rica has been strongly influenced by hundreds of foreign naturalists and scientists who have carried out exploration, research, and publication activities in relation to its biodiversity. Objective: To better understand their contributions, in this paper we take an historical tour, with emphasis on the last century and a half, regarding the motivations that attracted these people to Costa Rica, as well as their specific scientific contributions. Methods: Six criteria were followed to address this issue: a) whether they were residents or itinerants; b) if they had a frequent relationship with Costa Rica; c) if they collected specimens; d) the type of publication; and e) whether to implement teaching or institutional management. Results: Therefore, the information is organized into six large sections, structured chronologically as follows: the first inventories of the biodiversity of Costa Rica (1513-1842), the recognition of biological sciences in Costa Rican culture (1839-1848), the insertion of biological sciences in Costa Rican culture (1854-1886), the institutionalization of the biological sciences in Costa Rica (1886-1900), Costa Rica as a mecca for biological explorations (1900-1957), and the training of professionals in biological sciences (1940-2021). Conclusion: This periodization allows us to contextualize the contributions of those naturalists or scientists in time, as well as to better visualize the economic, social and political events and circumstances that conditioned their scientific work.